2018
DOI: 10.1159/000485842
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survivor Characteristics in Hemodialysis Patients with Type 2 Diabetes

Abstract: Background: Data concerning long-term mortality predictors among large, purely diabetic hemodialysis collectives are scarce. Methods: We used data from a multicenter, prospective, randomized trial among 1,255 hemodialysis patients with type 2 diabetes mellitus (T2DM) and its observational follow-up study. The association of 10 baseline candidate variables with mortality was assessed by Cox proportional hazards regression. Results: Overall, 103 participants survived the median follow-up of 11.5 years. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…However, age and retinopathy were the only risk factors for all-cause mortality among the subcohort of DM patients, and only age was predictive of CV mortality. In line with our results, a study on the characteristics of patients with DM that survived up to 11 years on HD showed that the risk of mortality increased by 3% per year increase in age [39]. Moreover, diabetic retinopathy was previously identified as an independent predictor of 3-year all-cause mortality among HD patients [40].…”
Section: Discussionsupporting
confidence: 90%
“…However, age and retinopathy were the only risk factors for all-cause mortality among the subcohort of DM patients, and only age was predictive of CV mortality. In line with our results, a study on the characteristics of patients with DM that survived up to 11 years on HD showed that the risk of mortality increased by 3% per year increase in age [39]. Moreover, diabetic retinopathy was previously identified as an independent predictor of 3-year all-cause mortality among HD patients [40].…”
Section: Discussionsupporting
confidence: 90%
“…Findings from observational studies are inconsistent. Although the study with the longest follow-up showed a clear association between high glycated hemoglobin and all-cause mortality, 16 this relationship was found to be either only in patients younger than 60 years 17 or without support. 18 In addition to the unclear accuracy of measures of glycated hemoglobin in dialysis patients, 19 assessments can be challenged by hypoglycemia, which is similarly associated with adverse events.…”
Section: Discussionmentioning
confidence: 90%
“…The relationship between blood pressure during dialysis and mortality risk is U-shaped, with both elevated and low post-dialysis SBP levels being associated with a higher risk of cardiovascular death, and the mortality is significantly increased when the DBP is greater than 109 mmHg [14]. MACCEs are important causes of death in uremic patients during MHD [15]. In this study, patients with uremia and refractory hypertension were included and the incidence of MACCEs was found to be 48.08%, similar to the results of previous studies [16].…”
Section: Discussionmentioning
confidence: 99%